Reengineering the Sharing Economy (Cambridge University Press, 2024)
This book explores some of the foundational theories for developing the next generation of sharing economy, one that is more equitable, democratic, sustainable, and just. It uses cross-disciplinary thinking to re-engineer the sharing economy through co-design of technology and regulation. This book is available as Open Access on Cambridge Core.